MODERATING EFFECT OF AGE AND GENDER ON LEARNED HELPLESSNESS AND JOB ATTITUDE RELATIONSHIP (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Employees are the biggest resource for the  organization. All the strategies of the organization  are implemented with the help of human  resources. Thus it becomes important to ensure  that human resources are satisfied and take  active participation regarding matters related  to their job. Nowadays employees want some  autonomy related to their work. If the employee  feels powerless they may experience learned  helplessness. Learned Helplessness at working  environment can leads to disengagement, role  stress, and agitated employee. This study aims  at analyzing the relationship between learned  helplessness and job attitudes. Results indicate  that there exists a negative relationship between  learned helplessness and job satisfaction and job  involvement. Further, gender has a moderating  effect on the impact of learned helplessness on  job involvement.
Keywords: Helplessness; Satisfaction; Involvement